University Reputation in the relationship between Service Quality and Learner’s Behavioral Intention - Bui Huy Khoi, Nguyen Thi Ngan (International Journal of Advanced Science and Technology, 2020)
This research aims to identify the relationship between university reputation, service quality, and learner’s behavioral intention in the context of education. Survey data was collected from 334 students studying in the high-quality program of Industrial University of Ho Chi Minh City. The research model was proposed from the studies about educational service quality, university reputation, and learner’s behavioral intention. The reliability and validity of the scale were tested Composite Reliability (Pc) and Average Variance Extracted (Pvc). The analysis results of the model showed that the educational service quality had a relationship with university reputation, and the behavioral intention had no relationships with the educational service quality and university reputation.